THE INFLUENCE OF LITERACY AND FINANCIAL INCLUSION ON INVESTMENT DECISIONS IN GENERATION Z IN MALAUSMA DISTRICT - Ari Susanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The potential of the younger generation, particularly Generation Z, as investors is truly remarkable. With their advanced technological skills, they possess the ability to become key players in driving investment development in Indonesia. Achieving true financial inclusion is closely tied to financial literacy. This study investigates the influence of financial literacy and financial inclusion on investment decisions among Generation Z in the Malausma District of Indonesia. The data utilized in this study consists of primary and secondary data obtained through questionnaires and literature reviews. The sampling method employed was non-probability sampling with a purposive sampling technique. To determine the sample size, the Lemeshow formula was utilized, resulting in 97 respondents, which was rounded up to 100. The data analysis technique involved instrument testing (validity and reliability), multiple linear regression analysis, and hypothesis testing (t-test, f-test, determinant coefficient/R2) using the SPSS Version 25 application. The findings of this research indicate that both financial literacy (X1) and financial inclusion (X2), both individually and collectively, have a positive and significant impact on investment decisions (Y) among Generation Z in the Malausma District.